IMPLEMENTASI SISTEM PENYIRAMAN UNTUK PENURUNAN SUHU PADA KUMBUNG JAMUR TIRAM PUTIH - Priyosa, Ifur (Jurnal Elektro Kontrol (ELKON), 2024)
Water is an abundant and easily accessible resource in everyday life. Water can be used to lower the temperature in a room, such as lowering the temperature in a white oyster mushroom cage. The aim of this research is to design a watering system that will be used to reduce the temperature in white oyster mushroom mushrooms. The method used is RD (Research And Development), which is a method of developing or creating new tools. In this study, 2 12v DC pumps and 30 sprayers with 0.6mm nozzles were used. The results of this research are that the temperature reduction is influenced by the duration of spraying, initial temperature, etc. Spraying based on a temperature setting point of 28°c takes 13 to 5 minutes with the highest temperature being 32.3. The minute water consumption is 2.2 liters per minute.